Electrolyte additive and electrolyte for aluminum electrolytic capacitor

By adding polyethylene glycol methyl ether end-capped substances to the electrolyte of the aluminum electrolytic capacitor, the capacitor deterioration and failure problems caused by the accumulation of various gases in the electrolyte are solved, and the capacitor life and performance improvement are achieved.

CN113838671BActive Publication Date: 2025-04-15DONGGUAN DONGYANG SOLAR SCI RES & DEV CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202010580520.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-06-23
Publication Date
2025-04-15
Estimated Expiration
2040-06-23

AI Technical Summary

Technical Problem

The gases such as ammonia, H2S, CO2, COS, CH4, CH2O, CH3OCH3 produced by the electrolyte used in aluminum electrolytic capacitors during the operation cause deterioration and failure of capacitor parameters. The existing hydrogen-depleting agent can only eliminate hydrogen and cannot eliminate other gases.

Method used

Polyethylene glycol methyl ether end-capped substances are used as electrolyte additives, which can adsorb and absorb ammonia and other volatile small molecular gases, prevent them from escaping and reduce the internal pressure of the capacitor.

Benefits of technology

It significantly extends the service life of aluminum electrolytic capacitors, reduces the probability of valve failure, improves the high temperature resistance of the electrolyte, and reduces the temperature rise and loss of the capacitor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113838671B_ABST
    Figure CN113838671B_ABST
Patent Text Reader

Abstract

The present invention provides an electrolyte additive for aluminum electrolytic capacitors and an electrolyte containing the additive. The additive is a polyethylene glycol methyl ether end-capping substance, and its structure is shown in formula (I) or (II), wherein n is 10-10000; the sum of x, y, and z is 10-10000, and at most one of x, y, and z is 0. The additive can be used to prevent the escape of ammonia and to protect the electrolyte containing C α H β O γ N δ S ε The volatile small molecules can be effectively absorbed, and the electrolyte containing it can reduce the probability of valve failure of aluminum electrolytic capacitors and significantly extend the service life of capacitors. n CH3(I)
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of aluminum electrolytic capacitors, and in particular relates to an electrolyte additive for aluminum electrolytic capacitors and an electrolyte for aluminum electrolytic capacitors containing the additive. Background Art

[0002] At present, the working electrolyte of aluminum electrolytic capacitors, whether it is water-based (low pressure) or organic-based (medium and high pressure), will inevitably produce a variety of gas-like chemical substances during the production and use of capacitors, and the continuous accumulation of gases will cause the capacitor parameters to deteriorate or even cause direct failure due to the opening of the explosion-proof valve. Therefore, in order to obtain products with long life and high performance, it is often necessary to add chemical additives that can interact with gases to the electrolyte. For example, the common dehydrogenating agent in the electrolyte formula is mainly used for the absorption of hydrogen.

[0003] The sources of gas in capacitors known to date are mainly the following:

[0004] (1) During the manufacturing process of aluminum electrolytic capacitors, the oxide film at the edge of the anode foil and the riveted joint with the lead bar or guide pin is often damaged due to cutting, piercing or other treatments. Such damage can be repaired to a certain extent by the electrolyte during the aging process, but the repair process of the oxide film is accompanied by the generation and release of cathode hydrogen. The specific reaction formula is as follows:

[0005] 2Al+3H2O-6e - →Al2O3+6H + (Anode) 6H + +6e - →3H2↑(cathode)

[0006] (2) The working electrolyte formula often contains ammonia or ammonium ions. When the capacitor is used at high temperature, ammonia may volatilize due to the increase in temperature and release ammonia gas. On the one hand, the released ammonia gas accumulates inside the capacitor, causing the internal pressure to increase, increasing the risk of product valve failure. On the other hand, ammonia gas means a change in the working electrolyte formula to a certain extent, which will also have an adverse effect on the properties of the capacitor;

[0007] (3) The working electrolyte contains various main solutes and additives. These chemical substances will also undergo chemical reactions during the high-temperature life test of the capacitor to produce various gases. For example, the thermal decomposition reaction of the main solute: RCOONH4→RCOOH+NH3; various long-chain organic molecules may crack under long-term high temperature and electric field to produce C α H β O γ N δ S εVolatile small molecules (where α, β, γ, δ, and ε take values ​​of 0 to 2, respectively) form complex mixed gases, such as H2S, CO2, COS, CH4, CH2O, CH3OCH3, etc.

[0008] In summary, the electrolyte for aluminum electrolytic capacitors will produce hydrogen, ammonia, H2S, CO2, COS, CH4, CH2O, CH3OCH3 and other gases during operation. However, the commonly used dehydrogenating agents are only used to eliminate hydrogen and have no effect on other gases. Therefore, it is necessary to develop an electrolyte additive that can eliminate gases other than hydrogen. Summary of the invention

[0009] In view of the gases such as ammonia, H2S, CO2, COS, CH4, CH2O, CH3OCH3 etc. generated by the electrolyte for aluminum electrolytic capacitors during operation, the present invention provides a novel additive polyethylene glycol methyl ether end-capping substance. The polyethylene glycol methyl ether end-capping substance can be used to prevent the escape of ammonia and to protect the electrolyte containing C α H β O γ N δ S ε The volatile small molecules (where α, β, γ, δ, and ε are 0 to 2 respectively) can be effectively absorbed. The electrolyte containing it can reduce the probability of valve failure of aluminum electrolytic capacitors and significantly extend the service life of capacitors.

[0010] In order to achieve the above object, the present invention adopts the following technical solutions:

[0011] In a first aspect, the present invention provides an electrolyte additive for aluminum electrolytic capacitors, wherein the additive is a polyethylene glycol methyl ether end-capping substance, and its structure is shown in formula (I) or (II):

[0012] CH3O(CH2CH2O) n CH3 (I);

[0013]

[0014] Wherein, n is 10-10000; the sum of x, y, and z is 10-10000, and at most one of x, y, and z is 0.

[0015] When NH4 +When NH3 is produced due to high temperature and its own instability, the polyethylene glycol methyl ether capping substance can adsorb NH3 to prevent it from overflowing and volatilizing, so that the reaction of ammonia generation is reversed or the forward reaction is hindered, thereby playing a role in fixing ammonia; a large number of ether groups in the polyethylene glycol methyl ether capping substance can form hydrogen bonds with small organic molecules, so it can absorb gases such as H2S, CO2, COS, CH4, CH2O, CH3OCH3, etc., thereby playing a role in fixing ammonia and absorbing gas in the electrolyte.

[0016] The size of the degree of polymerization of the polyethylene glycol methyl ether end-capping substance has an important influence on the absorption of gas. The inventor found in the experimental process that the larger the degree of polymerization, the stronger the adsorption of small molecule gases in the electrolyte, but the larger the degree of polymerization, the greater the viscosity of the electrolyte, and the macromolecules in the electrolyte will also hinder ion migration, thereby reducing the conductivity of the electrolyte, increasing the loss of the capacitor, and causing the capacitor to heat up when loaded and the performance to decrease. Therefore, in the present invention, the degree of polymerization n of the polymer shown in formula (I) is controlled at 10-10000, and the sum of the degrees of polymerization x, y, and z of the polymer shown in formula (I) is controlled at 10-10000.

[0017] According to some embodiments provided by the present invention, the n is 100-10000.

[0018] In some embodiments, n is 500-10000; in some embodiments, n is 500-5000; in other embodiments, n is 1000-10000; in other embodiments, n is 1000-5000.

[0019] Specifically, n can be exemplified by 10, 50, 100, 200, 300, 500, 800, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, 2000, 2100, 2200, 2300, 2400, 2500, 2600, 2700, 2800, 2900, 3000, 3100, 3200, 3300, 3400, 3500, 3600 00, 3700, 3800, 3900, 4000, 4100, 4200, 4300, 4400, 4500, 4600, 4700, 4800, 5000, 5200, 5500, 5800, 6000, 6200, 6500, 6800, 7000, 7200, 7500, 7800, 8000, 8200, 8500, 8800, 9000, 9200, 9500, 9800, 10000.

[0020] According to some implementation modes provided by the present invention, the sum of x, y and z is 100-10000, and x, y and z are not zero.

[0021] In some embodiments, the sum of x, y, and z is 500-10000; in some embodiments, the sum of x, y, and z is 500-5000; in other embodiments, the sum of x, y, and z is 1000-10000; in other embodiments, the sum of x, y, and z is 1000-5000.

[0022] Specifically, the sum of x, y, and z can be listed as: 10, 50, 100, 200, 300, 500, 800, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, 2000, 2100, 2200, 2300, 2400, 2500, 2600, 2700, 2800, 2900, 3000, 3100, 3200, 3300, 3400, 350 0, 3600, 3700, 3800, 3900, 4000, 4100, 4200, 4300, 4400, 4500, 4600, 4700, 4800, 5000, 5200, 5500, 5800, 6000, 6200, 6500, 6800, 7000, 7200, 7500, 7800, 8000, 8200, 8500, 8800, 9000, 9200, 9500, 9800, 10000.

[0023] On the other hand, the present invention also provides an electrolyte for aluminum electrolytic capacitors, comprising a polyethylene glycol methyl ether end-capping substance additive represented by formula (I) or (II).

[0024] According to some embodiments provided by the present invention, the additive is added in an amount of 0.1 to 6.0% based on the total weight of the electrolyte being 100%. Polymers are macromolecular organic substances. When the content of polymers in the electrolyte is high or exceeds a certain amount, the viscosity of the electrolyte increases sharply, which not only significantly increases the loss of the capacitor and causes severe heat generation, but also the electrolyte with a high viscosity is prone to impregnation during the impregnation process, which increases the safety risk and defective rate of the capacitor.

[0025] Specifically, they can be listed as: 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 19%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3. 0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5.0%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6.0%.

[0026] According to some embodiments provided by the present invention, the additive is added in an amount of 0.5 to 5.0%.

[0027] According to some embodiments provided by the present invention, the additive is added in an amount of 1.5 to 5.0%.

[0028] According to some embodiments provided by the present invention, the electrolyte further includes: solute, solvent and other additives.

[0029] The solute is not particularly limited, and any solute known in the art that can achieve the same or equivalent technical effects can be used in the present invention.

[0030] According to some embodiments provided by the present invention, the solute includes inorganic acids and salts thereof, organic acids and salts thereof.

[0031] The inorganic acid salt solute may be one or more of boric acid, phosphoric acid, ammonium borate, ammonium phosphate, ammonium hypophosphite, and the like.

[0032] The organic acid salt solute may be one or more of ammonium adipate, ammonium azelaate, ammonium sebacate, ammonium dodecanedioate, 2-butylammonium suberate, 2,7-dibutylammonium suberate, 1,4-dibutylammonium adipate, ammonium benzoate, ammonium citrate, and the like.

[0033] The solvent is not particularly limited, and any solvent known in the art that can achieve the same or equivalent technical effects can be used in the present invention.

[0034] According to some embodiments provided by the present invention, the solvent includes a main solvent and an auxiliary solvent.

[0035] The main solvent is usually an alcohol solvent, and the auxiliary solvent is usually an ether solvent.

[0036] Specifically, the main solvent can be one or more alcohol solvents such as ethylene glycol, diethylene glycol, propanol, 1,2-propylene glycol, n-butanol, butanediol, pentanol, isopentanol, pentanediol, hexanol, and hexylene glycol, preferably alcohols that are stable and non-volatile at room temperature.

[0037] Specifically, the auxiliary solvent may be one or more of diethylene glycol monobutyl ether, diethylene glycol monomethyl ether, butyl ether, propylene glycol methyl ether, dipropylene glycol methyl ether, tripropylene glycol methyl ether, and the like.

[0038] The other additives include corrosion inhibitors, waterproofing agents, flash enhancers, hydrogen removers, etc.

[0039] Specifically, the corrosion inhibitor may be one or more of mannitol, N,N-dimethylacetamide, o-nitrobenzamide, p-methyl-o-nitroaniline, and the like.

[0040] The waterproof mixture can be one or more of ammonium hypophosphite, phosphoric acid, ammonium phosphate, diammonium phosphate, and the like.

[0041] The flash enhancer may be one or more of polyvinyl alcohol, polyethylene glycol, nano silicon dioxide, silane coupling agent and the like.

[0042] The hydrogen remover is one or more of resorcinol, p-nitrophenol, p-nitrobenzyl alcohol, p-benzoquinone and the like.

[0043] According to some embodiments of the present invention, the electrolyte comprises: based on the total weight of the electrolyte as 100%, 0.1-6.0% of polyethylene glycol methyl ether capping substance, 3.0-15% of solute, 1.0-7.0% of corrosion inhibitor, 0.01-0.5% of waterproofing mixture, 0.5-15% of flash enhancer, 0.5-2.8% of hydrogen scavenger, 2.5%-10% of auxiliary solvent, and the balance of main solvent.

[0044] In some embodiments, the electrolyte includes: based on the total weight of the electrolyte as 100%, 0.5-5.0% of polyethylene glycol methyl ether capping substance, 3.0-15% of solute, 1.0-7.0% of corrosion inhibitor, 0.01-0.5% of waterproofing mixture, 0.5-15% of flash enhancer, 0.5-2.8% of hydrogen scavenger, 2.5%-10% of auxiliary solvent, and the balance of main solvent.

[0045] In another aspect, the present invention provides an aluminum electrolytic capacitor comprising the above-mentioned electrolyte.

[0046] Compared with the prior art, the present invention has the following technical effects:

[0047] (1) In the present invention, the polyethylene glycol methyl ether end-capping substance contains a large number of ether groups, and the ethyl group as an electron-donating group can enhance the activity of the ether group, so that it can form intermolecular forces such as hydrogen bonds with ammonium ions and small molecular compounds containing carbon, hydrogen and sulfur, thereby effectively absorbing ammonia and organic small molecular compounds generated by the degradation and decomposition of aluminum electrolytic capacitor electrolyte at high temperature, thereby improving the comprehensive performance of the electrolyte.

[0048] (2) In the present invention, adding polyethylene glycol methyl ether end-capping additives to the working electrolyte can effectively improve the high temperature resistance of the electrolyte, mainly through the additive adsorbing NH4 in the electrolyte. + , preventing it from overflowing and generating NH3, maintaining the stability of the electrolyte. When the working electrolyte with the additive is stored at 125°C for 250h, the change in electrolyte parameters is significantly reduced, especially the change in conductivity does not exceed -10%; while the change in conductivity of the electrolyte without the additive is greater than -35% under the same conditions.

[0049] (3) In the present invention, polyethylene glycol methyl ether end-capping additives are added to the working electrolyte, and the load life of the aluminum electrolytic capacitors produced is significantly extended, and the temperature rise is significantly reduced. After a 105°C load life test, the life test of the aluminum electrolytic capacitors with the working electrolyte containing the additive can be greater than 3500h, and no leakage or explosion occurs; while when the life test of the capacitors without the additive electrolyte reaches 2000h, multiple capacitors leak; and the temperature rise of the aluminum electrolytic capacitors with the working electrolyte containing the additive during the load life is about 2.0°C lower than that of the capacitors without the additive electrolyte.

[0050] (4) In the present invention, the internal pressure of the aluminum electrolytic capacitor produced by adding polyethylene glycol methyl ether end-capping additives to the working electrolyte is significantly reduced. After a 105°C / 2000h load life test, the bottom bulge height of the capacitor with the electrolyte containing the additive is reduced by about 40% compared with the capacitor without the electrolyte containing the additive. DETAILED DESCRIPTION

[0051] Unless otherwise specified, all scientific and technological terms used in the present invention have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. All patents and publications related to the present invention are incorporated herein by reference in their entirety. The term "comprising" or "including" is an open expression, that is, including the contents specified in the present invention, but does not exclude contents in other aspects.

[0052] The composition of the electrolyte provided by the present invention is described below according to the examples. It should be noted that the following description is intended to make the present invention clearer and should not be construed as limiting the present invention.

[0053] According to some embodiments provided by the present invention, the present invention provides an electrolyte for aluminum electrolytic capacitors, the electrolyte comprising: based on the total weight of the electrolyte as 100%, 0.1-6.0% of polyethylene glycol methyl ether capping substance, 3.0-15% of solute, 1.0-7.0% of corrosion inhibitor, 0.01-0.5% of waterproof mixture, 0.5-15% of flash enhancer, 0.5-2.8% of hydrogen remover, 2.5%-10% of auxiliary solvent, and the balance of main solvent.

[0054] The structure of the polyethylene glycol methyl ether end-capping substance is shown in formula (I) or (II):

[0055] CH3O(CH2CH2O) n CH3 (I);

[0056]

[0057] Wherein, n is 10-10000; the sum of x, y, and z is 10-10000, and at most one of x, y, and z is 0.

[0058] According to some embodiments provided by the present invention, the n is 100-10000.

[0059] In some embodiments, n is 500-10000; in some embodiments, n is 500-5000; in other embodiments, n is 1000-10000; in other embodiments, n is 1000-5000.

[0060] Specifically, n can be exemplified by 10, 50, 100, 200, 300, 500, 800, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, 2000, 2100, 2200, 2300, 2400, 2500, 2600, 2700, 2800, 2900, 3000, 3100, 3200, 3300, 3400, 3500, 3600 00, 3700, 3800, 3900, 4000, 4100, 4200, 4300, 4400, 4500, 4600, 4700, 4800, 5000, 5200, 5500, 5800, 6000, 6200, 6500, 6800, 7000, 7200, 7500, 7800, 8000, 8200, 8500, 8800, 9000, 9200, 9500, 9800, 10000.

[0061] According to some implementation modes provided by the present invention, the sum of x, y and z is 100-10000, and x, y and z are not zero.

[0062] In some embodiments, the sum of x, y, and z is 500-10000; in some embodiments, the sum of x, y, and z is 500-5000; in other embodiments, the sum of x, y, and z is 1000-10000; in other embodiments, the sum of x, y, and z is 1000-5000.

[0063] Specifically, the sum of x, y, and z can be listed as: 10, 50, 100, 200, 300, 500, 800, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, 2000, 2100, 2200, 2300, 2400, 2500, 2600, 2700, 2800, 2900, 3000, 3100, 3200, 3300, 3400, 350 0, 3600, 3700, 3800, 3900, 4000, 4100, 4200, 4300, 4400, 4500, 4600, 4700, 4800, 5000, 5200, 5500, 5800, 6000, 6200, 6500, 6800, 7000, 7200, 7500, 7800, 8000, 8200, 8500, 8800, 9000, 9200, 9500, 9800, 10000.

[0064] In some embodiments, the amount of the polyethylene glycol methyl ether end-capping substance added is 0.5-5.0%; in other embodiments, the amount of the polyethylene glycol methyl ether end-capping substance added is 1.5-5.0%.

[0065] Specifically, the addition amount of the polyethylene glycol methyl ether capping substance can be listed as: 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 19%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8 %, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5.0%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6.0%.

[0066] The solute is not particularly limited, and any solute known in the art can be used in the present invention.

[0067] According to some embodiments provided by the present invention, the solute includes an inorganic acid and a salt thereof, an organic acid and a salt thereof.

[0068] The inorganic acid salt solute may be one or more of boric acid, phosphoric acid, ammonium borate, ammonium phosphate, ammonium hypophosphite, and the like.

[0069] The organic acid salt solute is one or more of ammonium adipate, ammonium azelaic acid, ammonium sebacate, ammonium dodecanedioate, 2-butylammonium suberate, 2,7-dibutylammonium suberate, 1,4-dibutylammonium adipate, ammonium benzoate, and ammonium citrate.

[0070] The main solvent is usually an alcohol solvent, and the auxiliary solvent is usually an ether solvent.

[0071] Specifically, the main solvent is one or more of ethylene glycol, diethylene glycol, propanol, 1,2-propylene glycol, n-butanol, butanediol, pentanol, isopentanol, pentanediol, hexanol, and hexanediol.

[0072] Specifically, the auxiliary solvent is one or more of diethylene glycol monobutyl ether, diethylene glycol monomethyl ether, butyl ether, propylene glycol methyl ether, dipropylene glycol methyl ether, and tripropylene glycol methyl ether.

[0073] Specifically, the corrosion inhibitor is one or more of mannitol, N,N-dimethylacetamide, o-nitrobenzamide, and p-methyl-o-nitroaniline.

[0074] The waterproof mixture is one or more of ammonium hypophosphite, phosphoric acid, ammonium phosphate, and diammonium phosphate.

[0075] The flash enhancer is one or more of polyvinyl alcohol, polyethylene glycol, nano silicon dioxide and silane coupling agent.

[0076] The preparation method of the electrolyte is not particularly limited and can be carried out according to any method known in the art.

[0077] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. In the examples, if no specific conditions are specified, the conditions described in the specification, normal conditions or conditions recommended by the manufacturer are followed. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0078] The performance testing method used in the embodiment of the present invention is as follows:

[0079] 1. High-temperature storage and testing method of electrolyte: Different electrolytes were stored in a constant temperature oven at 125°C for 250 hours, and the moisture change rate, conductivity change rate, and pH change rate of different electrolytes before and after high-temperature storage were tested.

[0080] Moisture change rate (%) = (moisture content after storage - moisture content before storage) / moisture content before storage * 100;

[0081] Conductivity change rate (%) = (conductivity after storage - conductivity before storage) / conductivity before storage * 100;

[0082] pH change rate (%) = (pH after storage - pH before storage) / pH before storage * 100.

[0083] 2. Capacitor life test and temperature rise test method: capacitors with different electrolytes are made respectively, 4 samples are taken from each, and load life test is carried out in a 105℃ constant temperature convection oven; at the same time, the internal temperature rise of the capacitor is tested. The temperature rise test method uses a thermocouple inserted from the bottom of the capacitor to test the core package center temperature of the capacitor during the load life process.

[0084] Capacitor temperature rise (℃) = capacitor core center temperature - ambient temperature

[0085] Loss change rate (%) = 100*(loss after life test - initial loss) / initial loss

[0086] 3. The internal pressure of the capacitor is determined by the degree of bulging at the bottom of the capacitor.

[0087] Capacitor bulging degree (mm) = capacitor height after 2000h life test - capacitor initial height.

[0088] Comparative Example 1

[0089] The aluminum electrolytic capacitor electrolyte provided in this comparative example has the following components:

[0090] 62.5g of ethylene glycol; 8.5g of diethylene glycol monobutyl ether; 3.0g of boric acid, 5.5g of mannitol, 5.6g of ammonium azelaic acid, 2.0g of ammonium dodecanedioate, 0.5g of ammonium hypophosphite; 2.4g of p-nitrobenzoic acid; 10.0g of nano-silicon dioxide.

[0091] Example 1

[0092] The aluminum electrolytic capacitor electrolyte provided in the embodiment has the following components:

[0093] Ethylene glycol 62.0g; diethylene glycol monobutyl ether 8.5g; boric acid 3.0g, mannitol 5.5g, ammonium azelate 5.6g, ammonium dodecanedioate 2.0g, ammonium hypophosphite 0.5g; p-nitrobenzoic acid 2.4g; nano-silicon dioxide 10.0g; polyethylene glycol methyl ether capping substance 0.5g, the structure is CH3O (CH2CH2O) 2000 CH3(I-3).

[0094] Example 2

[0095] The aluminum electrolytic capacitor electrolyte provided in the embodiment has the following components:

[0096] Ethylene glycol 61.0g; diethylene glycol monobutyl ether 8.5g; boric acid 3.0g, mannitol 5.5g, ammonium azelate 5.6g, ammonium dodecanedioate 2.0g, ammonium hypophosphite 0.5g; p-nitrobenzoic acid 2.4g; nano-silicon dioxide 10.0g; polyethylene glycol methyl ether capping substance 1.5g, the structure is CH3O (CH2CH2O) 2000 CH3(I-3).

[0097] Example 3

[0098] The aluminum electrolytic capacitor electrolyte provided in the embodiment has the following components:

[0099] 59.5g of ethylene glycol; 8.5g of diethylene glycol monobutyl ether; 3.0g of boric acid, 5.5g of mannitol, 5.6g of ammonium azelaic acid, 2.0g of ammonium dodecanedioate, 0.5g of ammonium hypophosphite; 2.4g of p-nitrobenzoic acid; 10.0g of nano-silicon dioxide; 3.0g of polyethylene glycol methyl ether end-capping substance, the structure is CH3O (CH2CH2O) 2000 CH3(I-3).

[0100] Example 4

[0101] The aluminum electrolytic capacitor electrolyte provided in the embodiment has the following components:

[0102] Ethylene glycol 56.5g; diethylene glycol monobutyl ether 8.5g; boric acid 3.0g, mannitol 5.5g, ammonium azelate 5.6g, ammonium dodecanedioate 2.0g, ammonium hypophosphite 0.5g; p-nitrobenzoic acid 2.4g; nano-silicon dioxide 10.0g; polyethylene glycol methyl ether capping substance 6.0g, the structure is CH3O (CH2CH2O) 2000 CH3(I-3).

[0103] The electrolytes of Comparative Example 1 and Examples 1-4 were subjected to a high temperature storage test (125°C, 250h) and a load life test after being made into capacitors. The basic parameters of the electrolytes before and after the high temperature storage test included moisture, conductivity and pH; during the capacitor load life test, the life time, temperature rise, capacitor bulging degree and loss and other parameters for judging the comprehensive performance of the capacitor were tested, and the results are shown in Table 1.

[0104] Table 1

[0105]

[0106] As shown in Table 1, after adding the polyethylene glycol methyl ether end-capping additive, the electrolyte parameters change significantly reduced when the working electrolyte was stored at 125°C for 250 hours, especially the conductivity change did not exceed -10%; while the conductivity change of the electrolyte without the additive under the same conditions was greater than -35%. This is because the additive can absorb NH4 + , preventing it from overflowing to generate NH3, thereby effectively improving the high temperature resistance of the electrolyte.

[0107] The electrolyte was made into capacitors for load life tests. As shown in Table 1, the temperature rise of the aluminum electrolytic capacitor with the additive working electrolyte during the load life is about 2.0°C lower than that of the capacitor without the additive electrolyte. In addition, after a 105°C / 2000h load life test, the bulging height of the bottom of the capacitor with the additive electrolyte is about 40% lower than that of the capacitor without the additive electrolyte.

[0108] As shown in Table 1, the amount of polyethylene glycol methyl ether end-capping additives added to the electrolyte has a certain influence on the performance of the electrolyte and capacitor. As the additive content increases, the overall performance of the capacitor tends to improve, but when the addition amount exceeds 6.0%, the overall performance of the capacitor decreases. This is mainly because the more the amount added, the more the viscosity of the electrolyte will increase significantly, thereby reducing the conductivity of the electrolyte and affecting the impregnation efficiency during the capacitor manufacturing process; even excessive polymer additives will cause the core package to be unable to penetrate, resulting in increased capacitor losses and severe internal heating.

[0109] Example 5-11

[0110] The structure of polyethylene glycol methyl ether end-capping substances is as follows:

[0111] CH3O(CH2CH2O) 600 CH3 (I-1)

[0112] CH3O(CH2CH2O) 1000 CH3 (I-2)

[0113] CH3O(CH2CH2O)5000 CH3 (I-4)

[0114] CH3O(CH2CH2O) 10000 CH3 (I-5)

[0115]

[0116] The aluminum electrolytic capacitor electrolyte provided in the embodiment has the following components:

[0117] Ethylene glycol 61.0g; diethylene glycol monobutyl ether 8.5g; boric acid 3.0g, mannitol 5.5g, ammonium azelaic acid 5.6g, ammonium dodecanedioate 2.0g, ammonium hypophosphite 0.5g; p-nitrobenzoic acid 2.4g; nano-silica 10.0g; polyethylene glycol methyl ether end-capping substance 1.5, the structure of the polyethylene glycol methyl ether end-capping substance is shown in Table 2.

[0118] Comparative Example 2

[0119] The aluminum electrolytic capacitor electrolyte provided in this comparative example has the following components:

[0120] Ethylene glycol 61.0g; diethylene glycol monobutyl ether 8.5g; boric acid 3.0g, mannitol 5.5g, ammonium azelate 5.6g, ammonium dodecanedioate 2.0g, ammonium hypophosphite 0.5g; p-nitrobenzoic acid 2.4g; nano-silicon dioxide 10.0g; polyethylene glycol methyl ether capping substance 1.5g, the structure is CH3O (CH2CH2O) 20000 CH3(I-6).

[0121] The electrolytes of Comparative Example 2, Example 2, and Examples 5-11 were subjected to a high-temperature storage test at 125°C for 250 hours and a load life test after being made into capacitors. The basic parameters of the electrolytes before and after the high-temperature storage test included moisture, conductivity, and pH; during the capacitor load life test, parameters for judging the comprehensive performance of the capacitors, such as life time, temperature rise, capacitor bulging, and loss, were tested, and the results are shown in Table 2.

[0122] Table 2

[0123]

[0124] It can be seen from Table 2 that with the increase of the degree of polymerization of polyethylene glycol methyl ether end-capping additives, the high-temperature storage performance of the electrolyte has an upward trend, and the conductivity and pH change rate are significantly reduced; at the same time, after being made into a capacitor and subjected to a load life test, the overall performance of the capacitor also has an upward trend, the life is extended, and the temperature rise, loss change and capacitor bulging are significantly reduced. However, the larger the molecular weight, the greater the viscosity of the electrolyte, thereby reducing the conductivity of the electrolyte; and for polymers, the larger the molecular weight means the wider the molecular structure distribution, the worse the batch stability of the additive, and the more difficult it is to guarantee the performance. It can also be found from Table 2 that when the total degree of polymerization of polyethylene glycol methyl ether end-capping additives exceeds 10,000, the overall performance of the capacitor decreases. Therefore, it is necessary to select polyethylene glycol methyl ether end-capping additives with a suitable degree of polymerization, which can significantly improve the overall performance of the capacitor.

[0125] Although the present invention has been described in detail and some specific examples have been listed, it is apparent to those skilled in the art that various adjustments made to the present method are deemed to be included within the scope of the present invention as long as they do not depart from the spirit of the present invention.

[0126] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0127] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

Claims

1. An electrolyte additive for aluminum electrolytic capacitors, characterized in that: The additive is a polyethylene glycol methyl ether end-capping substance, and its structure is shown in (II): The sum of x, y, and z is 100-10000, and at most one of x, y, and z is 0.

2. The electrolyte additive for aluminum electrolytic capacitors according to claim 1, characterized in that: The sum of x, y and z is 500-10000.

3. The electrolyte additive for aluminum electrolytic capacitors according to claim 1, characterized in that: The sum of x, y and z is 1000-10000.

4. The electrolyte additive for aluminum electrolytic capacitors according to claim 1, characterized in that: The sum of x, y and z is 1000-5000.

5. An electrolyte for an aluminum electrolytic capacitor, characterized in that: The electrolyte additive for aluminum electrolytic capacitors comprises the electrolyte additive according to any one of claims 1 to 4.

6. The electrolyte for aluminum electrolytic capacitor according to claim 5, characterized in that: Based on the total weight of the electrolyte being 100%, the amount of the additive polyethylene glycol methyl ether end-capping substance added is 0.1-6.0%.

7. The electrolyte for aluminum electrolytic capacitor according to claim 5, characterized in that: Based on the total weight of the electrolyte being 100%, the amount of the additive polyethylene glycol methyl ether end-capping substance added is 0.5-5.0%.

8. The electrolyte for aluminum electrolytic capacitor according to claim 5, characterized in that: Based on the total weight of the electrolyte being 100%, the amount of the additive polyethylene glycol methyl ether end-capping substance added is 1.5-5%.

9. The electrolyte for aluminum electrolytic capacitor according to claim 5, characterized in that: The electrolyte further includes: a solute, a solvent and other additives; the solvent includes a main solvent and an auxiliary solvent.

10. The electrolyte for aluminum electrolytic capacitor according to claim 9, characterized in that: The other additives include corrosion inhibitors, waterproofing agents, flash enhancers and hydrogen removers.

11. The electrolyte for aluminum electrolytic capacitor according to claim 10, characterized in that: The electrolyte comprises: based on the total weight of the electrolyte being 100%, 0.1-6.0% of polyethylene glycol methyl ether end-capping substance, 3.0-15% of solute, 1.0-7.0% of corrosion inhibitor, 0.01-0.5% of waterproof mixture, 0.5-15% of flash enhancer, 0.5-2.8% of hydrogen remover, 2.5%-10% of auxiliary solvent, and the balance of main solvent.

12. The electrolyte for aluminum electrolytic capacitor according to claim 10, characterized in that: The electrolyte comprises: based on the total weight of the electrolyte being 100%, 0.5-5.0% of polyethylene glycol methyl ether end-capping substance, 3.0-15% of solute, 1.0-7.0% of corrosion inhibitor, 0.01-0.5% of waterproof mixture, 0.5-15% of flash enhancer, 0.5-2.8% of hydrogen remover, 2.5-10% of auxiliary solvent, and the balance of main solvent.

13. An aluminum electrolytic capacitor, characterized in that: An electrolyte for an aluminum electrolytic capacitor comprising any one of claims 5 to 12.

Citation Information

Patent Citations

  • Electrolyte for electrolytic capacitor

    JP1997106931A